Analysis of the wind effect on the patio cover (awning) structure in Malaysia - Nur'Atikah , Ab Rahman (2013)
Recently numbers of the damage and injuries due to wind hazard on the patio cover structure increases in Malaysia. Patio cover is defined any overhead covering constructed in an elevated position over a patio or deck with the intent to provide shade or rain coverage for the patio area. In Malaysia, this structure is constructed using steel structure and commonly notified as awning. Most of the awning structures are not well design. Therefore, the study are conduct to indicate the possibly of failure due to wind load. The typical type of patio cover used in Malaysia had been discovered as model 1, model 2 and model 3. The analysis carried out covering various loading and geometry configuration. The values that choose from the design that commonly used in Malaysia. From the result, it shows that the awning structure will fail at wind speed ii m/s for a few awning structures. It can be conclude that any structure needs to design properly to withstand from wind storm.